AB1012 Knowledge and Use of Derivation Pathways from Primary Health Care To Onset Arthritis Outpatient Clinics. Improvement Strategies. (15th July 2016) - Perez Venegas, J.J.; Cabello Fernandez, Y.; Rodriguez Valls, M.J.; Aranda-Valera, C.; Toledo Coello, M.D.
Abstract : Background: Among the factors that allow early diagnosis of recent-onset arthritis, there is the implementation of preferential derivation pathways from Primary Health Care (PHC). For 18 months, the Rheumatology unit from Health Area North of Cadiz (HANC) provides these routes (WEB/FAX) with criteria agreed with PHC. We analyze the opinion of primary care physicians on the need for early diagnosis of arthritis, degree of knowledge and use of these tools by PHC and collect proposals for improving the accessibility of these patients to our unit. Objectives: To analyze the level of knowledge and use of the preferential derivation pathways from primary care physicians to onset arthritis outpatient clinics; assess the satisfaction of the response received from the doctor and the importance of early diagnosis of rheumatoid arthritis for primary care physicians and collect proposals for improvement. Methods: Sharing a survey to primary care physicians from HANC serving 411, 000 habitants. Demographics of respondents, uptime in the public health system, number of patients seen per day, % estimated of musculoeskeletal pathology patients treated per day, importance of early diagnosis of rheumatoid arthritis and motives, level of knowledge of preferential derivation pathways collected by FAX/WEB, degree of utilization of these pathways, assessment and utility response received and proposals for improvement. A descriptive analysis of the sample is performed. Results: A total of 77 surveys from 13 Health Centers from HANC were analyzed. The 62.34% were men and 66.1% older than 50 years; 62% of respondents has worked in the public health system over 20 years. 88.3% (68) professionals attend over 40 patients/day and 40.2% (31) of respondents reported that 20–30% of consultations were musculoskeletal cause. 96.1% (74) of respondents gave importance to the early detection of arthritis, the main reason to avoid joint damage and improvement in quality of life (84.4%) and the establishment of an early treatment (79.2%). 87.01% (67) was unaware of the preferential derivation pathways through the web and 38.9% (30) knew via FAX. Only 19 doctors (24.6%) respondents acknowledged having used the pathway in the past 6 months; 17 of them (22.08%) considered appropriate response received. 97.4% of respondents considered helpful the existence of these preferential derivation pathways. Between strategies for improvement, 81.2% (63) propose conducting training and outreach campaigns, 88.31% (68) raises the need for training sessions and 79.2% (61) considered necessary conducting face consultations in health centers. Conclusions: A high percentage of primary care physicians surveyed recognize the importance of early diagnosis of recent-onset arthritis. Despite having preferential derivation pathways, there is a high degree of ignorance and low utilization of them. However, professionals who use them regard the response perceived as adequate. Most respondents believe that conducting training, outreach and onsite consulting and improvement strategies for early diagnosis of arthritis onset are necessary. Disclosure of Interest: None declared